PENGARUH BRAND IMAGE DAN POSITIONING SAMSUNG SMARTPHONE TERHADAP PERILAKU BRAND SWITCHING (STUDI KASUS PADA MAHASISWA UNIVERSITAS DIPA MAKASSAR) - Jannah, Fachriyahthul; Muamilah, Husnul (Patria Artha Management Journal, 2022)
This research aims to ascertain of brand image and positioning strategies for brand switching of Samsung smartphone. To find out how the influence of independent variables (brand image and positioning) of the dependent variable (brand switching) This research used multiple regression analysis with t test analysis method and F test. variables of independent brand image (X1) has no correlation with the dependent variable (brand switching). And the most dominant variables influencing brand switching is positioning with variable coefficient is 5.859. Coefficient of determination (Adjusted R2) is 0,338, shows that all the variable of positioning strategies have contributed jointly for 33.8% of the dependent variable (Y) brand switching behavior. Whereas the other 66,2% is explained by other variables. Through the F test can be seen that all the independent variables are adequate to test dependent variable. Hypothesis testing using t test showed that of the two independent variables, only positioning variables found to significantly influences the dependent variable.